Usutu virus infection in Dutch blood donors. Issue 9 (4th July 2019) - Zaaijer, Hans L.; Slot, Ed; Molier, Michel; Reusken, Chantal B.E.M.; Koppelman, Marco H.G.M.
Abstract : BACKGROUND: The screening of Dutch blood donations for West Nile virus (WNV) may be imminent, as WNV emerges in nearby countries and more donors travel to WNV‐affected regions. Since 2016 the related, mosquito‐borne Usutu virus (USUV) causes seasonal mortality in Dutch birds. To what extent will human USUV infections affect Dutch WNV donor screening? STUDY DESIGN AND METHODS: From April through September 2018, plasma samples from blood donations in blackbird‐rich regions were stored. When increased bird mortality was reported in August, samples from July, August, and September were tested for USUV‐RNA in pools of eight, using a home‐brew combined WNV/USUV‐PCR assay. Reactive pools were deconstructed. Original plasma units and samples of previous and follow‐up donations of reactive donors were tested for USUV‐ and WNV‐RNA, and for antibody responses. RESULTS: The number of USUV RNA‐positive, WNV RNA‐negative donations was 0 of 2688 donations in July, 6 of 4416 in August (1:736), and 1 of 4936 in September. The seven infected donors tested negative for USUV‐RNA in preceding and follow‐up donations. For 6 donors, seroconversion for USUV‐antibodies was demonstrated. All index donations tested positive in a commonly used PCR‐assay for WNV donor screening. Three exposed recipients did not show signs of infection. Screening a random subset of 1092 donations from September for USUV‐IgG antibodies showed that 22 donors tested reactive; for three donors retrospective testing identified an USUV PCR‐positive pre‐seroconversion donation. CONCLUSION: Seasonal USUV infection in Dutch blood donors is common. Cross‐reactivity in molecular assays for WNV‐screening occurs, but can be resolved using USUV‐ and WNV‐specific PCR‐primers and sequencing of viral RNA.